The Relationship between Ownership Structure and Capital Structure: Evidence from Chemical Sector of Pakistan - Sadia Murtaza; Irsa Azam (SEISENSE Journal of Management, 2019)
Objective – The main objective of this study is to measure the relationship between ownership structure and capital structure by using the chemical sector of Pakistan. Design – This study is used the panel data and retrieved from the annual reports of the chemical sector of Pakistan for the time period of 2012 to 2017. Findings – The finding the statistical analysis shows that ownership structure has a significant positive relationship on capital structure. Which mitigate the agency conflicts among managers and shareholders, because the majority of the shareholders would like to have a higher level of debt over equity financing. Policy Implications – The findings of this study also can be helpful to the policymakers, investors and financial institution in designing ownership structures and financing decisions for firms. Originality – This is the first study that examined the relationship between ownership structure and capital structure in the context of the chemical sector of Pakistan.